Gestão democrática, educação e cidadania: um olhar crítico a partir de fontes bibliográficas - Dias, Adriana Marques Guimarães [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The democratic management of education in Brazil emerged from social movements of teachers who demanded a public school education, universal, secular and free in the 1980s that sense, democratic management countered to the school administration, which gradually ceased to be part of educational literature on the subject, as well as education laws (SILVA JUNIOR, 2002). So, in the face of social pressures, democratic management has become a legal principle in the Federal Constitution of 1988, which was then reflected in the Ten Year Plan for Education (1993), in LDBEN 9394/96, the National Education Plan - 2001-201, unfolding in the Education Development Plan - PDE (Adrião & Camargo, 2007; Saviani, 2006, 2008). Therefore, we sought to understand what ideological implications underlay the amendment. Therefore, we have adopted procedures of literature (GIL (2002)), using Brazilian authors of literary texts on business administration (TAYLOR (1856-1915), Fayol (1841-1925), CHIAVENATO (1983), Motta (1991), TRAGTEMBERG (1974), school administration (FELIX (1989), LION ARIES (1887-1966), SON LORENZO (1897-1970), QUERINO RIBEIRO (1907-1990), Teixeira (1900-1971), Myrtes Alonso (1976), BRUNO (1997)), school management (SANDER, (2005), PARO (2010)) and democratic management (ARROYO (2008), PARO (2003, 2008), VEIGA (1995), LUCK (2000 ), SILVA JUNIOR (2002)) and the above laws and guidelines of multilateral organizations such as the Economic Commission for Latin America and the Caribbean (ECLAC), the International Monetary Fund (IMF) and the World Bank (WB), that produced documents as the Priorities and Strategies for Education: sectoral World Bank study, and the United Nations Educational, Science and Culture (UNESCO), responsible for organizing the World Conference on Education for All and the document World Declaration on Education for All - Meeting the Basic Learning Needs, in 1993. In addition, we rely on academic research on the ...

La gestion démocratique de l'éducation au Brésil a émergé des mouvements sociaux des enseignants qui réclamaient un enseignement public, universel, laïque et gratuite dans les années 1980 ce sens, la gestion démocratique a répliqué à l'administration de l'école, qui a cessé progressivement de faire partie de littérature éducative sur le sujet, ainsi que les lois de l'éducation (SILVA JUNIOR, 2002). Donc, face à des pressions sociales, la gestion démocratique est devenu un principe juridique dans la Constitution fédérale de 1988, qui a ensuite été traduit dans le Plan décennal pour l'éducation (1993), dans LDBEN 9394/96, le Plan national d'éducation - 2001-201, qui se déroule dans l'éducation au développement régime - PDE (Adrião & Camargo, 2007; Saviani, 2006, 2008). Par conséquent, nous avons cherché à comprendre ce qui sous-tendaient implications idéologiques de l'amendement. Par conséquent, nous avons adopté des procédures de la littérature (GIL (2002)), en utilisant auteurs brésiliens de textes littéraires sur l'administration des affaires (TAYLOR (1856-1915), Fayol (1841-1925), Chiavenato (1983), Motta (1991), TRAGTEMBERG (1974), l'administration scolaire (FELIX (1989), LION ARIES (1887-1966), fils Lorenzo (1897-1970), Querino RIBEIRO (1907-1990), Teixeira (1900-1971), Myrtes Alonso (1976), Bruno (1997)), la gestion de l'école (SANDER, (2005), PARO (2010)) et de la gestion démocratique (ARROYO (2008), PARO (2003, 2008), Veiga (1995), la chance (2000 ), SILVA JUNIOR (2002)) et les lois ci-dessus et les lignes directrices des organisations multilatérales telles que la Commission économique pour l'Amérique latine et les Caraïbes (CEPALC), le Fonds monétaire international (FMI) et la Banque mondiale (BM), que les documents produits comme les «Priorités et stratégies pour l'éducation: sectorielle étude de la Banque mondiale», et l'Organisation des Nations Unies pour l'éducation, la ...

A gestão democrática da educação no Brasil surgiu dos movimentos sociais de professores que reivindicavam uma educação escolar pública, universal, laica e gratuita na década de 1980. Nesse sentido, a gestão democrática contrapôs-se à administração escolar, que paulatinamente deixou de fazer parte da literatura educacional sobre o tema, bem como das legislações de ensino (SILVA JUNIOR, 2002). Então, diante das pressões sociais, a gestão democrática tornou-se um princípio legal na Constituição Federal de 1988, que depois se refletiu no Plano Decenal da Educação (1993), na LDBEN 9394/96, Plano Nacional da Educação - 2001-201, desdobrando-se no Plano de Desenvolvimento da Educação - PDE (ADRIÃO & CAMARGO, 2007; SAVIANI, 2006, 2008). Sendo assim, buscamos compreender quais implicações ideológicas embasaram tal alteração. Para tanto, adotamos procedimentos da pesquisa bibliográfica (GIL (2002)), utilizando-se de textos da literatura de autores brasileiros sobre administração de empresas (TAYLOR (1856-1915), FAYOL (1841-1925), CHIAVENATO (1983), MOTTA (1991), TRAGTEMBERG (1974), administração escolar (FELIX (1989), CARNEIRO LEÃO (1887-1966), LOURENÇO FILHO (1897-1970), QUERINO RIBEIRO (1907-1990), ANÍSIO TEIXEIRA (1900-1971), Myrtes Alonso (1976), BRUNO, (1997)), gestão escolar (SANDER, (2005), PARO (2010)) e gestão democrática (ARROYO (2008), PARO (2003, 2008), VEIGA (1995), LUCK (2000), SILVA JUNIOR (2002)), bem como as legislações supracitadas e as orientações dos organismos multilaterais como: a Comissão Econômica para América Latina e o Caribe (CEPAL), o Fundo Monetário Internacional (FMI) e o Banco Mundial (BM), que produziram documentos como as Prioridades e estratégias para a Educação: estudo setorial do Banco Mundial, e a Organização das Nações Unidas para Educação, a Ciência e a Cultura (UNESCO), responsável pela organização da Conferencia Mundial de Educação...
Democratic management, education and citizenship: a critical look from literature sources
Keywords: Gestão democrática; Escolas - Organização e administração; Sociedade civil; Neoliberalismo; Education